The acceptance to heterologous booster vaccination of COVID-19 vaccine among HCWs and targeted population: A cross-sectional study in central China - Qin, Wei; Zhang, Xiaqing; Wang, Yao; Pan, Fan; Cheng, Kai; Huang, Fangfang; Song, Jian; Su, Hong (Frontiers in Public Health, 2022)
Background: There are few studies reported on the acceptance of heterologous booster vaccination for the COVID-19 vaccine among healthcare workers (HCWs) and the general population. We aimed to address that gap and explore determinant factors of acceptance of the heterologous booster vaccination. Methods: We conducted a cross-sectional study to examine the prevalence and determinant factors of the acceptance of heterologous booster vaccination for the COVID-19 vaccine among HCWs and the targeted population. Results: A total of 364 HCWs and 1898 targeted populations were investigated in our study. 76.4% HCWs would recommend heterologous booster vaccination to their patients and 59.8% targeted population endorsed a clear willingness to receive this strategy. Compared with the adenoviral vector vaccine (AD5-nCOV), recombinant protein vaccine (ZF2001) was more preferred by HCWs (79.1%) and the targeted population (72.0%) as a heterologous booster vaccine. HCWs who did not work in the vaccination clinics were more likely to recommend heterologous booster vaccination (OR=3.3, CI: 1.5-7.3). The targeted population aged 18-59 years (OR=1.5, 95%CI:1.1-2.3), had a positive attitude towards COVID-19 vaccination (OR=3.8, 95%CI:1.7-8.6), had confidence in the safety of COVID-19 vaccines (OR=6.6, 95%CI:4.2-10.2), followed the recommendation of HCWs (OR=33.6, 95%CI:22.0-51.2), took initiative in collecting booster shots information (OR=2.1, 95%CI:1.5-3.0), and were familiar with the heterologous strategy (OR=1.9, 95%CI:1.1-3.1) were more likely to choose heterologous booster vaccination. The history of side effects of inactivated COVID-19 vaccine was a negative factor in choosing heterologous booster vaccination (OR=0.4, 95%CI:0.4-1.0). Conclusions: The heterologous booster vaccination strategy on the COVID-19 vaccine could be widely accepted among HCWs, whereas its acceptance among targeted population was only moderate. Public authorities should make efforts to communicate the public about the effectiveness and safety of the heterologous booster vaccination which could help increase their willingness to get vaccinated.